Pengaruh Pemberian Sitokinin Terhadap Pertumbuhan Palea dan Lemma Padi Melaui Kultur In Vitro - Kamsinah Kamsinah; Triani Hardiyati; Sugiyono Sugiyono (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2009)
A research has been carried out with the aims to: 1. study the influence of both the kind and concentration of cytokinins on palea and lemma growth in in vitro culture; 2. study the influence of palea and lemma age towards external application of cytokinin in in vitro culture; and3. determine the best palea-lemma age, kind and concentration of cytokinin which resulted the best growth of palea and lemma in in vitro culture. The used experimental method was Completely Randomised Design (CRD) with factorial treatment pattern. The applied treatment consisted of three factors i.e. palea-lemma age (U): (55, 60, and 65 days after planting); kind of cytokinin (S): (BAP and Kinetin); and Cytokinin Concentration (K): (0, 5, 10, and 15 M) with 3 replications. The observed variables were the palea and lemma growth with the parameters were palea-lemma length and width. The results showed that the kind of cytokinin had influenced the growth of palea-lemma in in vitro culture, and kinetin has better influence on the palea-lemma growth. The age of the palea-lemma determined the responsiveness of the palea-lemma towards external application of cytokinin. Older palea-lemma showed less responsive than younger ones towards external application of plant growth regulators. Moreover, the treatment combination (U1S2K2) (10 µM Kinetin applied to 55-day-old rice palea-lemma) had the best effect on increasing the size of palea-lemma of IR 64 rice.